CONFLICT MANAGEMENT IN ISLAMIC EDUCATIONAL INSTITUTIONS: PREVENTIVE AND RESOLUTIVE STRATEGIES - Goffar, Abdul; Afidah, Briliana (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
This research aims to examine forms of conflict and conflict resolution strategies implemented in formal Islamic education institutions. Through a qualitative approach and a case study type, data was obtained through observation, in-depth interviews and documentation studies. The research results showed that the conflicts that occurred were divided into three main categories: structural, interpersonal and inter-student conflicts. To prevent and resolve conflicts, madrasas implement preventive strategiessuch as policy outreach, communication training, job rotation, and active involvement of OSIM. Meanwhile, resolution strategies are carried out through mediation by the head of the madrasah, counseling by guidance and counseling teachers, as well as arestorative approach that emphasizes awareness and reconciliation. This approach is strengthened by the application of Islamic values such as islah, shura, and tabayyun. Evaluations show a reduction in conflict incidents, increased student satisfaction, andthe creation of a harmonious work atmosphere. This research concludes that conflict management that is integrated structurally, humanistically and spiritually is able to create a healthy, resilient and collaborative madrasah culture.